2022
DOI: 10.1038/s41431-022-01216-5
|View full text |Cite
|
Sign up to set email alerts
|

Genome-wide identification of disease-causing copy number variations in 450 individuals with anorectal malformations

Abstract: Anorectal malformations (ARM) represent a spectrum of rare malformations originating from a perturbated development of the embryonic hindgut. Approximately 60% occur as a part of a defined genetic syndrome or within the spectrum of additional congenital anomalies. Rare copy number variations (CNVs) have been associated with both syndromic and non-syndromic forms. The present study represents the largest study to date to explore the contribution of CNVs to the expression of ARMs. SNP-array-based molecular karyo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 29 publications
(38 reference statements)
0
1
0
Order By: Relevance
“…In human studies, the disruption of FOXK2 was found to be associated with central nervous system abnormalities and intellectual disability [ 39 ]. Using an SNP BeadChip, Fabian et al [ 40 ] identified some CNVs in a population with anorectal malformations (ARM) disease, confirmed the presence of nine submicroscopic CNVs using qPCR and suggested several genes, such as FOXK2 , as factors causing ARM disease. The mannose-binding lectin 2 ( MBL2 ) gene is one of the members of the C-type (Ca 2+ dependent) lectin gene superfamily and plays an important role in the first line of defense against pathogen infection [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In human studies, the disruption of FOXK2 was found to be associated with central nervous system abnormalities and intellectual disability [ 39 ]. Using an SNP BeadChip, Fabian et al [ 40 ] identified some CNVs in a population with anorectal malformations (ARM) disease, confirmed the presence of nine submicroscopic CNVs using qPCR and suggested several genes, such as FOXK2 , as factors causing ARM disease. The mannose-binding lectin 2 ( MBL2 ) gene is one of the members of the C-type (Ca 2+ dependent) lectin gene superfamily and plays an important role in the first line of defense against pathogen infection [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Chromosomal causes of ARMs represent 5 to 15% of the cases. They include aneuploidies (in particular trisomy 21 found approximately in 2% of ARM) and Copy Number Variations (CNV, approximately found in 3% of ARM) [5,7]. Monogenic variants explain up to 1/3 of syndromic ARMs, and are very heterogeneous [8].…”
Section: Introductionmentioning
confidence: 99%